PENINGKATAN HASIL BELAJAR MATEMATIKA SIMETRI LIPAT DAN PUTAR MELALUI MEDIA SPARKOL - Juniarsih, Winda; Hidayati, Yulia Maftuhah; Syamsiyah, Siti (CV Sintesia, 2025)
This study aims to study mathematics learning outcomes of folding and rotating symmetry using sparkol media. the research subjects who were subjected to action were students of class iii with a total of 19 students. methods of data collection using tests. the data analysis technique used is a qualitative descriptive technique which includes the stages of data reduction, data presentation and conclusion drawing. the results showed that there was an increase in student learning outcomes. and the increase in learning outcomes can be seen from the kkm that has been determined, namely 75, namely before the students' actions are completed, namely 2 with an average of 59.73, cycle i 8 with an average of 68.1, cycle ii students who complete 17 with an average of 77, 54. the conclusion of this study is that sparkol media can increase motivation and learning outcomes of grade iii students of sd muhammadiyah 4 kandangsapi in 2020/2021.